2017
DOI: 10.1002/adhm.201700465
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Wound Healing on Skin by Electrical Stimulation with a Bioelectric Plaster

Abstract: Wound healing on skin involves cell migration and proliferation in response to endogenous electric current. External electrical stimulation by electrical equipment is used to promote these biological processes for the treatment of chronic wounds and ulcers. Miniaturization of the electrical stimulation device for wound healing on skin will make this technology more widely available. Using flexible enzymatic electrodes and stretchable hydrogel, a stretchable bioelectric plaster is fabricated with a built-in enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…Electrical current at the wound site helps cell migration and proliferation and accelerates the wound‐healing process . Kai et al reported that the ionic current conducted through hydrogels promotes wound healing in vivo ( Figure ) . They show that wounds treated with a hydrogel bandage (group B) grow a thicker epidermis with a less stressed boundary compared with the control (group A).…”
Section: Hydrogels and Hydrophilic Polymersmentioning
confidence: 98%
See 1 more Smart Citation
“…Electrical current at the wound site helps cell migration and proliferation and accelerates the wound‐healing process . Kai et al reported that the ionic current conducted through hydrogels promotes wound healing in vivo ( Figure ) . They show that wounds treated with a hydrogel bandage (group B) grow a thicker epidermis with a less stressed boundary compared with the control (group A).…”
Section: Hydrogels and Hydrophilic Polymersmentioning
confidence: 98%
“…Group A control with traditional wound dressing; group B hydrogel wound dressing; group C uses ionic stimulation through the hydrogel. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Hydrogels and Hydrophilic Polymersmentioning
confidence: 99%
“…Electrical stimulation (ES) or electrotherapy is a noninvasive and pain‐free treatment, known to promote skin healing, that is of growing interest. This method has beneficial effects, especially in chronic wounds and ulcers, as it stimulates cell proliferation and migration thus accelerating the healing process . It has also been shown to stimulate dermal angiogenesis and keratinocyte proliferation .…”
Section: Therapeutic Strategies To Improve Wound Healing and Reinnervmentioning
confidence: 99%
“…This method has beneficial effects, especially in chronic wounds and ulcers, as it stimulates cell proliferation and migration thus accelerating the healing process. [81] It has also been shown to stimulate dermal angiogenesis and keratinocyte proliferation. [82,83] The principle of ES is to mimic the endogenous electric current that occurs during wound healing and for that purpose, it is essential to establish ideal and standardized protocol parameters such as: modality, method of delivery and duration of treatment.…”
Section: Electrostimulationmentioning
confidence: 99%
“…The creation of seamless interfaces between biological systems and multifunctional devices is a vital step towards the fabrication of next-generation wearable devices for applications in teleoperation, [1,2] medical treatments, [3,4] health monitoring, [57] and even personal entertainment [810] . Commercial wearable devices are either rigid (e.g., smart fitness watches), or soft but with determinant shapes (e.g., haptic gloves for virtual reality applications).…”
mentioning
confidence: 99%